2020
DOI: 10.3390/biology9040084
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Insurance and Marital Status on Survival in Patients with Nasopharyngeal Carcinoma

Abstract: Objective: This study aimed to explore the influence of social support on the survival outcomes of patients with nasopharyngeal carcinoma (NPC). We examined whether the combined proxy influenced whether patients were more likely to receive radiotherapy. Methodology: data were collected from the 18 registries of the National Cancer Institute’s Surveillance, Epidemiology, and End Results database. The association between both insurance status and marital status and disease-specific survival rates were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…This could be explained by the fact that socioeconomic psychological factors and genetic diversity might play an important role in tumorigenesis and tumor progression [18,19]. Several previous studies demonstrate that marital status and ethnicities were important etiological and prognostic factors in several solid tumors, including cervical cancer [20][21][22][23]. Similarly, in our study, better survival was seen in married patients and in white women.…”
Section: Discussionsupporting
confidence: 77%
“…This could be explained by the fact that socioeconomic psychological factors and genetic diversity might play an important role in tumorigenesis and tumor progression [18,19]. Several previous studies demonstrate that marital status and ethnicities were important etiological and prognostic factors in several solid tumors, including cervical cancer [20][21][22][23]. Similarly, in our study, better survival was seen in married patients and in white women.…”
Section: Discussionsupporting
confidence: 77%
“…This could be explained by the fact that socioeconomic psychological factors and genetic diversity might play an important role in tumorigenesis and tumor progression (20)(21)(22). Several previous studies did demonstrate that marital status and ethnicities were important etiological and prognostic factors in several solid tumors, including cervical cancer (23)(24)(25)(26). Similarly, in our study better survival was seen in married patients and in white women.…”
Section: Discussionsupporting
confidence: 74%
“…Wang et al demonstrated that uninsured, unmarried patients with NPC had a higher risk of metastases, were less likely to receive radiation, and had a poorer 5-year disease-specific survival rate than their insured, married counterparts. 9 Insurance status provides merely a proxy for SES. Another study found poorer overall survival of Taiwanese patients with NPC was associated with male sex, older age, and low income.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated links between factors involved in SES and survival in NPC. Wang et al demonstrated that uninsured, unmarried patients with NPC had a higher risk of metastases, were less likely to receive radiation, and had a poorer 5‐year disease‐specific survival rate than their insured, married counterparts 9 . Insurance status provides merely a proxy for SES.…”
Section: Discussionmentioning
confidence: 99%